Primary Conjunctival Basal Cell Carcinoma Mimicking an Ocular Surface Squamous Neoplasia in a Young Adult Filipino: A Case Report and Literature Review - Lorenz Jacob Mangahas; Rowena Wea Reyes; Richmond Siazon (Case Reports in Ophthalmological Medicine)
Conclusion: Primary BCC of the conjunctiva is rarely encountered, especially in young individuals, mimicking squamous neoplasia both in morphology and histopathology. Therefore, this should be considered in the differential diagnosis of OSSN. Immunostaining is crucial in differentiating between the two conditions and confirming the diagnosis. In most cases, wide surgical excision is sufficient. In addition, adjuvant therapies may be beneficial in preventing tumor recurrence.